Phenology of Parasetigena silvestris (Diptera: Tachinidae), gypsy moth (Lymantria dispar) (Lepidoptera: Lymantriidae) larval parasitoid and its efficiency for parasitisation. Issue 5 (4th May 2019) - Lee, Jang-Hoon; Pemberton, Robert W.
ABSTRACT: Parasetigena silvestris is a univoltine, solitary, larval endoparasitoid which lays its eggs on the surface of gypsy moth larvae. Field collection of the host larvae (2nd through 5th instar) from an artificially established gypsy moth population were made to compare stage specific parasitism between larvae without and with P. silvestris tachinid eggs. The tachinid oviposition rate detected was highest in second instar larvae, and then decreased as larvae developed toward full maturity. The opposite was true for tachinid parasitoid emergence which had no emergence from second through third host instar larvae. Fourth instar gypsy moth larvae, however, experienced significantly higher parasitism by P. silvestris in the larvae with eggs than those without the eggs. The braconid wasp Cotesia melanoscelus caused significantly higher parasitism in early instar larvae with P. silvestris eggs than in those without the eggs. The tachinid prefers to lay more eggs on parasitised larvae by the braconid even though the braconid is a superior competitor to the fly during multiparasitism. Factors influencing parasitism rates by P. silvestris such as host-parasitoid synchronisation and the multiparasitism interaction with C. melanoscelus are discussed.